Prevalence of Balantidium coli in Buffaloes at different areas of Mymensingh - Roy, BC; Mondal, MMH; Talukder, MH; Majumder, S (Journal of the Bangladesh Agricultural University, 2011)
Balantidium coli is a common protozoan disease of animals. A total of 151 buffaloes were examined through faecal examination, of which 68 (45.03%) found to be infected with B. coli infection. Prevalence of B. coli infection was relatively higher in adult buffaloes (49.52%) aged > 5 years than young (39.29%) aged > 2- ≤ 5 years and buffalo calves (27.78%) aged ≤ 2 years. Higher prevalence of B. coli was observed in female (47.32%) than that of male (38.46%) buffaloes which are not statistically significant. Prevalence of B. coli infection was significantly (p<0.01) higher in poor health buffaloes (78.95%) than healthy buffaloes (24.47%) and buffaloes reared in normal floor/muddy floor (46.21%) than that reared in concrete floor (36.84%), respectively. Significantly (p<0.05) higher prevalence of B. coli infection was observed in rainy season (60%) followed by summer (42.10%) and winter season (32.76%). It is concluded that buffaloes are highly susceptible to balantidiasis irrespective of age, sex, health status, management system and seasons of the year. Keywords: Balantidium coli; Prevalence; Buffaloes DOI: http://dx.doi.org/10.3329/jbau.v9i1.8746 JBAU 2011; 9(1): 67-72